Understanding the Effectiveness of Village Fund Allocation Management: A Study in Sinjai Regency - ST. Ramadania; Nur Asmi Ainun kamal (Income Journal Of Economics Development, 2024)
This research aims to analyze the effectiveness of managing village fund allocation in Sinjai Regency. The research method used is descriptive quantitative, involving data collection through observation and interviews, as well as the analysis of primary and secondary data. The results of the analysis show that the management of village fund allocation in Sinjai Regency is classified as effective, with an average level of effectiveness during the 2018-2022 period reaching 96.58%. This study underscores the importance of effective village resource management in enhancing the community economy and improving village infrastructure. The research results indicate that the government of Sinjai Regency has succeeded in achieving a high level of effectiveness in managing village funds, particularly in the development sector. Despite fluctuations, the average level of effectiveness of village fund management during the 2018-2022 period remains relatively high. Further analysis reveals that the management of village fund allocation in Sinjai Regency has met established effectiveness standards, with the effectiveness percentage peaking in 2018 and 2022. The findings of this research contribute to a better understanding of how village fund allocation is managed and its impact on development at the village level. This research plays a crucial role in enhancing knowledge about the effectiveness of village fund allocation management, and it provides valuable insights for village governments and related stakeholders to improve village fund management performance in the future.